1932
DOI: 10.1017/s0025315400051481
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Study of the Fauna of the Sandy Beach at Port Erin

Abstract: A survey of the sandy beach at Port Erin, Isle of Man, was made in. September, 1931. Observations were made, at a number of stations, involving simultaneous records of the macro-fauna and its density, and certain physical and chemical factors of the sand and interstitial water, as well as tidal level on the beach. The results enable certain general conclusions to be drawn as to the causes of the observed distribution of species, and of the differences between the faunas of this and some Scottish beaches. Plans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
1

Year Published

1936
1936
1979
1979

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 4 publications
1
19
0
1
Order By: Relevance
“…Pirrie, Bruce & Moore (1932) describe a similar zonation on the sandy beach at Port Erin. It is recorded from muddy sand at Salcombe by Allen & Todd (1900), and in the Mersey Estuary by Bassindale (1938).…”
Section: Nerine Cirratulus (Della Chiaje)mentioning
confidence: 85%
See 1 more Smart Citation
“…Pirrie, Bruce & Moore (1932) describe a similar zonation on the sandy beach at Port Erin. It is recorded from muddy sand at Salcombe by Allen & Todd (1900), and in the Mersey Estuary by Bassindale (1938).…”
Section: Nerine Cirratulus (Della Chiaje)mentioning
confidence: 85%
“…Populations on sandy and muddy shores have been described by Stephen (1929a), Elmhirst (1931), Pirrie, Bruce & Moore (1932), Rees (1939), Watkin (1942), and Brady (1943). Besides these general surveys, there have been more intensive studies of certain species, such as those of Stephen (1928Stephen ( , 1929aStephen ( , b, 1931Stephen ( , 1932 on the biology of Tellina tenuis and certain other lamellibranchs.…”
Section: Introductionmentioning
confidence: 99%
“…No interstitial salinities were recorded from beneath sea water, and it seems probable that Bruce was working in an area of surface drainage of fresh water. Pirrie, Bruce & Moore (1932) did not attach much importance to lowered interstitial 3-2 36 RALPH I. SMITH salinity at Port Erin, for they conclude that' rio very close correlation must be looked for between the distribution of the fauna and the salinity of the beach'. Emery & Foster (1948) have shown that the salt-water table in the sands.of exposed Californianbeaches rises and fallswith the tides, but lagging by 1-3 h and with decreasing amplitude as the land is approached.…”
Section: General Description Of the Beachmentioning
confidence: 96%
“…In both places it occurs abundantly from between low-water of neap and spring tides, downwards, and can be dredged in numbers close to the shore in depths of two to four metres. The general condition of the Port Erin sandy beach has been described by Pirrie, Bruce and Moore (1932) and by Moore (1933). Sea surface temperatures at Port Erin (being the mean monthly temperatures for the years are shown in Text Fig.…”
mentioning
confidence: 99%